Organisational Commitment Among Nurses: A qualitative study - Ana Luiza Ferreira Aydogdu (Asia Pacific Journal of Health Management)
Objective: To describe the perceptions and experiences related to the organisational commitment of nurses working in healthcare institutions across different regions of Brazil.